A comment on modelling the paleogeography of confined and unconfined marine Gilbert-type deltas. - Muto, T.; Okada, H. (Cuadernos de Geología Ibérica, 1991)
Geological records of marine Gilbert-type deltas, if poorly preserved, permit multiple reconstructions of the paleogeography. Erosional unconformities at the set bases, related to lateral confinement of the deltas, are one of the keys to the problem. The numerical model dealing with constant conditions indicates that (1) ancient lateral confinement cannot be reconstructed only from dxc pattern/shape of the delta-front curves, unless other basinal conditions have been estimated; (2) the delta front turns landwards at the early stage of the evolution even if any external factor would not change; (3) steady rises of relative sea-level unfavour vertical stacking of multiple sets of the deltas; and (4) the basal unconformities result from quick falis of relative sealevel, or from negative, high-gradient seaward delta-front vectors. Multiplystacked Oilbert-type systems associated with the unconformities and alluvialfan deposits can be interpreted to have prograded within fan-dissecting valleys which elongated along the maximum-slope direction of the basinmargrn area.